Optimalisasi Pemanfaatan Dana Desa Dalam pembiayaan Program pemberdayaan Masyarakat Desa Ilili Kecamatan Kesuy Watubela Kabupaten Seram Bagian Timur - Rumailili, Muh. Fauzan; Sahetapy, Petronela; Pattimukay, Hengky; Selanno, Hendry (LPPM Institut Pendidikan Nusantara Global, 2024)
Optimizing the Utilization of Village Funds in Financing Community Empowerment Programs in Ilili Village, Kesuy Watubela District, Eastern Seram Regency. The research results show that the use of village funds in financing community empowerment programs has not achieved optimal results, so it is important to follow up through focused and specific planning, implementation and control of programs that are oriented towards increasing community economic income. If the use of village funds in a procedural manner including planning, implementation and control is carried out optimally, the expected goals will be achieved in financing community empowerment programs and realizing community welfare in Ilili Village, Kesuy Watubela District, Eastern Seram Regency.